STRUCTURE OF FINANCIAL RESOURCES OF NON-STATE PENSION FUNDS IN UKRAINE AND THEIR ANALYSIS (Economic journal of Lesya Ukrainka Volyn National University, 2018)
The article studies that the structural characteristics of the financial resources of the non-governmental pension funds in legislation and domestic science are fragmented and often ambiguous. The essence of the notion «financial resources of a non-state pension fund» is defined as monetary resources (assets and liabilities) that perform the necessary internal and external functions and interact with monetary, social, insurance and banking systems.The paper analyzes the structure of assets of a non-state pension fund and gives the legislatively fixed directions of their investment. The structure of non-governmental pension funds liabilities, which are conditionally divided into primary and secondary ones, is analyzed. It is substantiated that the source of the formation of the main obligations of the non-governmental pension funds is accumulated pension contributions to individual accounts, and the source of coverage of secondary liabilities should be the investment income of the non-governmental pension funds.An empirical-statistical and graphical analysis of the dynamics of internal NPFs and their financial-resource base for 2009–2017 was conducted. The analysis showed that the largest activity in creating the non-governmental pension funds is demonstrated by enterprises of the real sector of the economy; although pension contributions tend to increase, they are not great. In turn, pension payments are growing faster than paid pension contributions, and carried out author’s calculations indicate that the accumulated pension contributions are very small, and amount to less than 1% of the annual volumes of own revenues of the Pension Fund of Ukraine. The volumes of the financial resources of non-governmental pension funds, in particular pension assets and investment income, are still insignificant for the large-scale diversification of pension assets into high-yield domestic and foreign financial instruments, although these volumes are constantly increasing. It has been investigated that the amount of expenses reimbursed by pension assets is significant, especially at the beginning of the operation of non-governmental pension funds.The recommendations for improving the activity of domestic non-state pension funds and improving the structure of their financial resources are given.
Keywords: financial resources; non-state pension fund; assets of non-state pension fund; an obligation of a non-state pension fund; pension contributions; retirement benefits.